1997
DOI: 10.1016/s0266-7681(97)80052-6
|View full text |Cite
|
Sign up to set email alerts
|

Registration Bone Scan in the Evaluation of Wrist Pain

Abstract: We assessed the value of bone scintigraphy combined with X-ray registration for the diagnosis and management of wrist pain in 65 patients. Studies were reported independently by two observers before and after registration. Registration improved localization of scan abnormalities in 53% (observer 1) and 61% (observer 2). In these patients, the bone scan contributed to the diagnosis independently of the X-ray in 37% and the management was altered in 31%. The value of the bone scan in the early diagnosis and mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Coregistration of bone scans with plain radiography has been reported as useful in the evaluation of hand pain/trauma, but the technique is challenging [56] and is not a widely used practice. Huellner et al [57] recently reported a pilot retrospective study of 21 patients with non-specific hand and wrist pain, comparing SPECT-CT with MRI.…”
Section: Applications Of Single Photon Emission Ct-ct In the Upper Limbmentioning
confidence: 99%
“…Coregistration of bone scans with plain radiography has been reported as useful in the evaluation of hand pain/trauma, but the technique is challenging [56] and is not a widely used practice. Huellner et al [57] recently reported a pilot retrospective study of 21 patients with non-specific hand and wrist pain, comparing SPECT-CT with MRI.…”
Section: Applications Of Single Photon Emission Ct-ct In the Upper Limbmentioning
confidence: 99%
“…Bone scintigraphy of the peripheral extremities is an excellent tool to detect orthopedic disorders [1][2][3][4][5][6][7][8][9][10][11][12][13][14][29][30][31]. However, the evidence on the value of hybrid imaging of the peripheral extremities is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports emphasize the high sensitivity of bone scintigraphy [1][2][3][4][5][6][7][8][9][10][11]. However, it is also well known that the specificity of bone scintigraphy is quite low due to the lack of anatomic information, especially in the peripheral extremities, although pinhole SPECT may improve the diagnostic accuracy of imaging the peripheral extremities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bone scintigraphy is frequently used for the diagnostic evaluation of orthopedic disorders because altered bone metabolism can be detected before morphologic changes are detected with planar radiography [8][9][10][11][12][13][14][15][16][17][18]. It is particularly valuable in evaluating prostheses of the hip joints and knees as their loosening leads to periprosthetic augmentation of bone metabolism, which is easily picked up by this technology [19].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence has accumulated with regard to the superiority of SPECT/CT over stand-alone SPECT in staging malignant disease [20][21][22]. Further, several papers have also explored its potential for studying patients with orthopedic disorders [8][9][10][11][12][13][14][15][16][17][18]. However, to the best of our knowledge, a larger trial on the value of this hybrid imaging technology in patients who had undergone lumbar instrumentation is still missing.…”
Section: Introductionmentioning
confidence: 99%